Hukum Perlindungan Konsumen dalam Produk Perbankan Digital: (Studi Kasus Dana) (International Forum of Researchers and Lecturers, 2024)
Based on the provisions in Law no. 7 of 1992 in conjunction with Law no. 10 of 1998 concerning Banking, commercial banks provide services such as transferring money according to the type of bank category. Along with the rapid development of technology and science in the era of globalization, the banking sector is also required to adapt to improve services to customers. Fintech, or financial technology, is designed to make financial services easier for people. However, potential threats remain and require preventive measures. This article reviews in depth legal protection for customers in digital financial transactions. This research uses a normative legal method with a literature study approach as a way of collecting data. The results of the descriptive analysis show regulations related to legal protection for customers in digital financial transactions with platforms such as DANA, as well as the role of LPS in maintaining the security of customer funds.